Learning from Each Other: Experience Sharing Workshop on Implementation of Smart Pack and CBBP among Ethiopian Public Universities - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A workshop geared towards understanding the status of universities in implementing CBBP in terms of CBBP village establishment and streamlining and uses of the integrated curricula with CBBP was conducted in two clusters ( May 31, 2023, in Bahir Dar) and ( June 1, 2023, in Adama). In addition, experience exchange through the presentation of universities in implementing CBBP was presented, and the background training was delivered on SmaRT pack (Small ruminant transformation packages associated with Feed and feeding, Health interventions, Genetic improvement, and livestock marketing by ICARDA and ILRI scientists. Five Universities in the first workshop (May 31, 2023) and three Universities in the second workshop (June 1, 2023) presented their status in implementing CBBP in their respective universities. Other Universities were also allowed to reflect on their status, followed by discussion and experience sharing. The training has covered the SmaRT pack (Small ruminant transformation packages) that has addressed genetic improvement, Feed development and intervention, health intervention and market channels, and enabling environments such as cooperative organization and capacity building that hastens small ruminant value chain to produce a quality product and improve the livelihood and food security status of the community. Twenty-nine Undergraduates and thirty-seven postgraduates (five Ph.D. and 32 M.Sc programs) have streamlined Community Breeding Program in the curricula and implemented teaching practices and knowledge products of CBBP ‘’ Guideline line for setting up the community-based small ruminant breeding program is in use as a reference material to teach animal breeding courses in all universities (Haile et al., 2020) and others were used as a reference material to teach Animal breeding courses in undergraduate and postgraduate programs. Community-based breeding program villages, which symbolize climate-smart agriculture, have been initiated under the universities' budgetary and technical support. More than 58 villages have been initiated under the support of 20 universities and mobilized more than 1 million USD. The villages serve as a learning site and sources of longitudinal data to hasten research and paved the way for demonstrating CBBP that showcased impactful community services through CBBP. Other universities are also in the progress of implementing CBBP activities based on the lessons of the champion universities. More than 4440 farmers are beneficiaries of CBBP initiatives, and more than 1400 students/year are beneficiaries of a streamlined CBBP in the curriculum. The key lessons captured in implementing CBBP in the university program includes showcasing other programs to have local data and practices in teaching resource and contribute to the quality and relevance of education, resource mobilization, and demonstrating the synergy of learning, research, and community services, ensuring teamwork to bring impactful community services and a continuous capacity building and provision of training materials which could be reflected in teaching and learning efforts of universities. There are also future activities that need to address, such as strengthening CBBPs and supporting the programs sustainably and scaling up the programs based on the scaling framework and reaching out to millions of small ruminant keepers, and improving food security and the income and livelihood of communities at household and community level. Fifty-six (two women) participants were part of the experience-sharing workshop in the two venues (Bahir Dar and Adama).